DISIPLIN KERJA SATUAN PENGAMANAN UNIVERSITAS NEGERI PADANG - Feri Syaputra (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research is to gather information about the work discipline. The population is 104 employees and the sample is 54 people taken by random sampling. The instrument of this research is questionnaire with Likert scale models that had been tested for validity and reliability. Data were analyzed by using mean score of performance. The result of this research shows that the work discipline Security Team for State Universiti of Padang is good enough. Key words : Security Team work discipline